Health promotion intervention for people with early‐stage dementia: A quasi‐experimental study - Testad, Ingelin (Brain Behav, 2020)
INTRODUCTION: With the limited advancements in medical treatment, there is a growing need for supporting people with early‐stage dementia adjust to their diagnosis and improve their quality of life. This study aimed to investigate the effects of a 12‐week health promotion course for people with early‐stage dementia. METHODS: Quasi‐experimental, single group, pretest‐posttest design. A total of 108 persons with dementia participated in this study, and for each participant, a carer was interviewed. The 12‐week health promotion intervention consisted of 2‐hr sessions at weekly intervals. Outcome measures were cognition, measured by Mini‐Mental State Examination, personal, and instrumental activities of daily living (P‐ADL and I‐ADL), measured by Lawton and Brody's Physical Self‐Maintenance Scale and Instrumental Activities of Daily Living Scale, self‐rated health, measured by the European Quality of life Visual Analogue Scale, depressive symptoms, measured by the Cornell Scale for Depression in Dementia, and neuropsychiatric symptoms, measured by The Neuropsychiatric Inventory. Assessments were conducted at baseline and at follow‐up 1–2 months postintervention. RESULTS: The results demonstrate a small but statistically significant improvement in depressive symptoms (p = .015) and in self‐rated health (p = .031). The results also demonstrated a small statistically significant decline in the participants’ I‐ADL (p = .007). The participants’ cognitive function, P‐ADL, and neuropsychiatric symptoms were stable during the 4‐month follow‐up. CONCLUSION: This study demonstrates promising results with regard to the benefit of attending a 12‐week health promotion intervention in promoting health and well‐being in people with early‐stage dementia. With the majority of participants with early‐stage dementia living at home without any healthcare services in a vulnerable stage of the condition, this study makes an important contribution to highlighting the need for, and benefit of, educational approaches for this population.